(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Stress prevalence increases by 5% in 15-year-olds and over in Surabaya. Stress causing negative effects is called distress. It may affect teenagers’ nutritional status without considering their diet, leading to growth inhibition if it occurs continuously. It follows Riskesdas’s (2013) data stating that 13-15-year-olds have a nutritional status of 3.3% very thin, 7.8% thin, 8.3% overnutrition, and 2.5% obese. Therefore, this study aimed to discover the relationship between stress level and nutritional status at SMP Negeri 56 Surabaya due to its dense academic and non-academic activities. Based on JPNN.com, several students hurt themselves using a blade due to psychological problems. Methods: This study used an observational analytical study design through a cross-sectional approach. Data collection was performed using the DASS-21 questionnaire and weight and height measurements, then analyzed using the Pearson Correlation or Rank Spearman test. Conclusion: the stress level was not related to the nutritional status of eighth-grade students of SMP Negeri 56 Surabaya, observed from the current nutritional status (BB/U), past nutritional status (TB/U), and body proportion (IMT/U).